Valuation structure in incomplete information contests: experimental evidence (2019)
We experimentally examine perfectly discriminating contests under three valuation structures: pure common-value, pure private-value and a case with both private and common value components. In line with the results from the previous literature, we find that, regardless of valuation structure, contestants often choose very conservative expenditures, and very aggressive expenditures. Average expenditures exceed Nash equilibrium predictions. In valuation structures with a common value component, contestants often choose expenditures in excess of the expected value of the prize conditional on winning the contest. That is, they often guarantee themselves negative payoffs in expectation. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.